Does self-initiated sit-to-stand training with an assistive device regain the independence of sit-to-stand in stroke patient? A single-blinded randomized controlled trial - Joey, Ng Chee Man (J Rehabil Assist Technol Eng, 2020)
BACKGROUND: It is unknown whether self-initiated sit-to-stand training with an assistive device is effective to regain the independence of sit-to-stand in stroke survivors. OBJECTIVE: To compare the effectiveness of self-initiated sit-to-stand training with an assistive device with manual sit-to-stand training. DESIGN: Parallel randomized controlled, assessor-blinded trial between January 2015 and May 2018. Randomization was performed by drawing lots to allocate treatment groups. SETTING: A rehabilitation hospital in Hong Kong. PARTICIPANTS: 69 participants in medical wards with unilateral hemiparetic stroke. A total of 52 participants fulfilled the study requirements. INTERVENTION: Ten sessions of intervention with conventional physiotherapy program followed, by self-initiated sit-to-stand training with an assistive device, or by manual sit-to-stand training. MAIN OUTCOME MEASURE: Number of participants regained the independence of sit-to-stand, sit-to-stand test from the Balance master® and Five-repetition sit-to-stand test. RESULTS: 69 participants (intervention, n = 36; control, n = 33) were randomized (mean age, 69.8 years (SD: 10.6), mean post-stroke days 18.6 (SD: 16.0)). Seventeen participants had not completed 10 sessions of training, leaving 52 (n = 26; n = 26) participants for per protocol analysis. Eighteen participants in the intervention group and 10 participants in the control group had regained the independence of sit-to-stand (Phi and Cramer’s V: –0.31 and 0.31). The participants in the intervention group were faster to complete the Five-repetition sit-to-stand test than the control group (32.7 sec (SD: 1.93) versus 48.4 sec (SD, 6.8); 95% confidence interval, –30.8 to –0.7; p < 0.05). No adverse side effects occurred during and after the training across groups. CONCLUSIONS: Self-initiated sit-to-stand training with an assistive device may have positive effects on speeding up regaining the independence of sit-to-stand on sub-acute stroke survivors.